Political message disruption in family communication patterns on social media - Zen Amirudin; Rachmah Ida; Irfan Wahyudi (Interaksi: Jurnal Ilmu Komunikasi, 2025)
This study examines the disruption of political messages within Family Communication Patterns (FCP) through social media in the context of the 2024 General Election in Blimbing District, Malang City. No study has specifically analyzed how algorithmic disruption shapes political message negotiation across the four FCP types. This research addresses this gap by providing the first empirical integration of Stuart Hall's encoding-decoding model with FCP typology in the Indonesian electoral context. Employing a qualitative approach with reception analysis methodology, the research involved 8 informants from 4 families representing pluralistic, protective, consensual, and laissez-faire types, with data collection through in-depth interviews, and participant observation. Findings reveal that social media has fundamentally transformed family political communication from a single-encoder model to a multiple-encoder ecosystem, wherein younger generations now function as primary decoders who re-encode political messages for parental consumption. Based on Hall's (1973) framework, the protective family demonstrated dominant-hegemonic reading characterized by uncritical acceptance of preferred meanings and rejection of counter-hegemonic messages; pluralistic and consensual families adopted negotiated reading through distinct mechanisms collaborative co-decoding via weekly political forums versus hierarchical decoding through family digest rituals respectively; the laissez-faire family exhibited fragmented individual reading without collective meaning-making processes; and no family fully adopted oppositional reading, although children in the protective family exhibited emerging oppositional tendencies triggering intergenerational conflicts over meaning-making authority. This study contributes to political communication scholarship by proposing "algorithmic encoding" as a third FCP dimension and a "distributed encoding-decoding framework," thereby extending Hall's model beyond mass media contexts into digitally-mediated family communication.